Circulação de prescrições para a formação da juventude rural no Brasil e nos Estados Unidos: a experiência dos Clubes 4-S e 4-H no pós Segunda Guerra Mundial - Leonardo Ribeiro Gomes (2019)
The aim of this thesis was to investigate the circulation of prescriptions to the formation of rural youth in the United States and Brazil, based on the experience the 4-H Clubs (Head, Hands, Heart, Health) and the Clubes 4-S (Saber, Sentir, Saúde, Servir)after the Second World War. The rural youth clubs had basically the same organizational structure. They were composed by rural youngsters, girls and boys, between the ages of 10 and 18 and have as the symbol a green four-leaf clover. The aim of the clubs was to reach the so-called life modernization of rural communities in the countries, having the youngsters as elements to disseminate a new sensibility in rural areas. By analyzing the organization of 4-H clubs it was possible to understand their ideas andproposals which expanded internationally through a series of institutions in the context studied that influenced, for example, the creation, formation, and expansion of the 4-S clubs in Brazil. The research shows that even though there was a general modelfor the clubs, there were different points between both experiences related to the social, political, and economic structures of each reality. One of them was about the type of rural leadership constituted from the youth clubs. It was possible to see thatthe diffusion of the rural extensionist idea in North American molds can be considered as one dimension of Americanism in Brazil. The research was based on the analysis of documents about the Serviços de Extensão Rural (Rural Outreach Services) and, mainly, the work of rural youth groups presented in books, magazines, newspapers, reports, programs, projects, plans, manual, booklets, letters, memos, posters, photographs, and other documents available in the archives of Centro de Documentação da EMATER-MG, Biblioteca Nacional de Agricultura do Brasil and electronic archives, such as the National Agricultural Library of the United States, the Rockefeller Archive Center, and the 4-H History Preservation.